2009
DOI: 10.1007/s00464-009-0665-2
|View full text |Cite
|
Sign up to set email alerts
|

Hospital volume as a surrogate for laparoscopically assisted colectomy

Abstract: Socioeconomic differences appear to exist between high- and low-volume hospitals in the use of laparoscopy. High hospital volume is associated with an increased likelihood that colectomy will be performed with laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Singla et al [2] concluded that socioeconomic differences appear to exist between high-and low-volume hospitals in the use of laparoscopy in the United States and that laparoscopic colectomy is more often performed in highvolume hospitals. Although the study by Singla et al [2] is limited by its retrospective nature, the proportion of laparoscopic colectomy in the United States still is small even in high-volume hospitals.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Singla et al [2] concluded that socioeconomic differences appear to exist between high-and low-volume hospitals in the use of laparoscopy in the United States and that laparoscopic colectomy is more often performed in highvolume hospitals. Although the study by Singla et al [2] is limited by its retrospective nature, the proportion of laparoscopic colectomy in the United States still is small even in high-volume hospitals.…”
mentioning
confidence: 98%
“…In the study by Singla et al [2], overall, only 8,407 of colon resections (4%) were performed using laparoscopy. The authors found that high-volume hospitals used laparoscopy more often than low-volume hospitals (5.2 vs. 3.4%).…”
mentioning
confidence: 98%
See 3 more Smart Citations